Pigeons (Columba livia) are a suitable experimental model for Neospora caninum infection in birds - Mineo, Tiago W. P. [UNESP]; Carrasco, Adriano O. T. [UNESP]; Marciano, Jose A. [UNESP]; Werther, Karin [UNESP]; Pinto, Aramis A. [UNESP]; Machado, Rosangela Z. [UNESP] (Elsevier B.V., 2009)
Neospora caninum infections in chickens have been recently described by epidemiological and experimental approaches, and these birds may be considered natural intermediate hosts of the parasite. It has been postulated that other bird species might perform this role in wildlife as well. To better understand the sylvatic life cycle of N. caninum, further studies are required. In that sense, this work aimed to observe infection kinetics in pigeons experimentally infected with N. caninum. Experimental infections were Conducted in parallel with a related protozoan, Toxoplasma gondii, which has been already described as able to infect pigeons in nature. Our results demonstrated that N. caninum disseminated through various tissues of this host and induced parasite-specific IgG seroconversion. Infection parameters were similar to that observed in the T. gondii infected group, although N. caninum-infected pigeons presented lower IgG titers during acute phase. The results herein described demonstrate that pigeons are a suitable model for N. caninum infection, considering that these data are in agreement with those observed in chickens experimentally infected with this parasite. As pigeons may be revealed as important reservoirs for N. caninum infection in nature, future Studies are necessary to determine the real prevalence of this parasite in this and other birds in wildlife. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Neospora caninum; Columba livia; Experimental infection; Infection model; Toxoplasma gondii